METHODOLOGICAL BASIS OF DESIGN OF THE CLOUD-BASED LEARNING AND RESEARCH ENVIRONMENT OF A HIGHER EDUCATION INSTITUTION - Shyshkina, М.П. (Journal of Information Technologies in Education (ITE), 2019)
The feasibility of using and implementing of the cloud data processing services into the educational process of a higher education institution in order to support educational and scientific activities is substantiated. The results of the analysis of modern psychological and pedagogical researches testify to a steady movement towards the search of new ways of creating and using educational software based on the concept of cloud computing, which significantly changes the means and approaches to the organization of pedagogical activity. The essence of the problem of formation and development of the cloud oriented learning and research environment of higher education institution is analyzed; the basic conceptual and terminological apparatus of the research is specified. It has been determined that in the cloud-oriented environment of a higher education institution, the computer processing activities of participants of educational processes are supported by cloud computing technology, which implies flexible use of a virtual hybrid or only public or corporate ICT infrastructure. The stages of designing a cloud-oriented environment are distinguished, among which there are the stages of pilot design and widespread implementation. The first stage involves the creation and experimental testing of a prototype of the environment. The second stage of design consists in the widespread implementation of the results of the pilot test, at this stage the basic regularities, characteristics and properties revealed in the first stage must be considered and summarized. Both stages have their components, in particular - target, structural-functional, resource, resulting. It is substantiated that in the process of designing it is advisable to rely on the developed system of models of formation and development of the cloud-oriented learning and research environment: the models of educational and scientific components; the general model of its formation and development, the model of grouping of components; the hybrid service model for organizing access to software. The content of a hybrid cloud-based service model encompasses electronic educational and research resources. The cloud-based component grouping model contains different types of services, among which it is advisable to distinguish the following main groups: generalpurpose services; communication services; specialized educational and research services. The results of the pilot design of a cloud-oriented educational and research environment of a higher education institution, carried out on the basis of joint research laboratories of the Institute of Information Technologies and Learning Tools of the National Academy of Educational Sciences of Ukraine and a number of higher education institutions are generalized.